In vivo proof-of-concept for two experimental antiviral drugs, both directed to cellular targets, using a murine cytomegalovirus model - Sonntag, Eric; Hahn, Friedrich; Bertzbach, Luca D.; Seyler, Lisa; Wangen, Christina; Müller, Regina; Tannig, Pierre; Grau, Benedikt; Baumann, Matthias; Zent, Eldar; Zischinsky, Gunther; Eickhoff, Jan; et al. (Antiviral Research, 2019)
Infections with the human cytomegalovirus (HCMV) cause serious medical problems including organ rejection and congenital infection. Treatment of HCMV infections with currently available medication targeting viral enzymes is often accompanied with severe side effects and the occurrence of drug-resistant viruses. This demands novel therapeutical approaches like targeting genetically stable host cell proteins that are crucial for virus replication. Although numerous experimental drugs with promising in vitro efficacy have been identified, the lack of available data in animal models limits their potential for further clinical development. Recently, we described the very strong in vitro antiherpesviral activity of the NF-κB inhibitor TF27 and the CDK7 inhibitor LDC4297 at low nanomolar concentrations. In the present study, we present first data for the in vivo efficacy of both experimental drugs using an established cytomegalovirus animal model (murine CMV replication in immunodefective Rag −/− mice). The main findings of this study are (i) a strong inhibitory potency against beta- and gamma-herpesviruses of both compounds in vitro, (ii) even more important, a pronounced anticytomegaloviral activity also exerted in vivo, that resulted from (iii) a restriction of viral replication to the site of infection, thus preventing organ dissemination, (iv) in the absence of major compound-associated adverse events. Thus, we provide evidence for a strong antiviral potency in vivo and proof-of-concept for both drugs, which may encourage their further drug development, possibly including pharmacologically optimized derivatives, for a potential use in future antiherpesviral treatment.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Antiviral drug development; Antiviral experimental drugs; Artemisinin and pyrazolotriazine compounds; Herpesviral in vitro/vivo models; Human and murine cytomegaloviruses; Proof-of-concept